The Mental Health of First-Year Medical Students in Universitas Baiturrahmah - Mutiara Anissa; Resti Rahmadika Akbar; Anita Darmayanti; Meta Oktora (HM Publisher, 2021)
Introduction. First-year students are a group that has experienced many changes in their lives. Studying in university requires students to be exposed to new challenges, namely academic demands, independence to meet needs and activities, and more independence in learning. Medical students have a heavier burden due to a dense curriculum, so that they will face various module exams, clinical skills, practicums, lectures, and other student organizational activities. If students are not able to adjust, then this can cause emotional mental disorders.Methods. This study was a cross-sectional design. Participants are new students of the 2020 in Faculty of Medicine, consist of the Medical Study Program and the Clinical Pharmacy Study Program. The research sample is total sampling. This research instrument uses a Self Reporting Questionnaire (SRQ). This questionnaire can measure the mental state of a person who has a 30 days time limit. Data processing using SPSS, univariate data is displayed in the form of a frequency distribution table.Results. In this study, most of the respondent have total SRQ less than 6 (80.8%). The symptoms of mental emotional disorders that are most commonly found are somatic symptoms and depressive symptoms.Conclusion. The mental health of Baiturrahmah medical students is still within the normal range, but mental health assessments need to be carried out every year.